A companion to ancient philosophy - Sanday, Eric; Kirkland, Sean D. (Evanston, Illinois : Northwestern University Press, 2018)
A Companion to Ancient Philosophy is a collection of essays on a broad range of themes and figures spanning the entire period extending from the Pre-Socratics to Plato, Aristotle, and the Hellenistic thinkers. Rather than offering synoptic and summary treatments of preestablished positions and themes, these essays engage with the ancient texts directly, focusing attention on concepts that emerge as urgent in the readings themselves and then clarifying those concepts interpretively. Indeed, this is a companion volume that takes a very serious and considered approach to its designated task-accompanying readers as they move through the most crucial passages of the infinitely rich and compelling texts of the ancients. Each essay provides a tutorial in close reading and careful interpretation. Because it offers foundational treatments of the most important works of ancient philosophy and because it, precisely by doing so, arrives at numerous original interpretive insights and suggests new directions for research in ancient philosophy, this volume should be of great value both to students just starting off reading the ancients and to established scholars still fascinated by philosophy's deepest abiding questions. -- Provided by publisher.
Introduction / Sean D. Kirkland and Eric Sanday -- Early Greek thinking: the emergence of philosophy : Physis in pre-Socratic thought: seeking with Xenophanes / Robert Metcalf -- Going with the flow: soul and truth in Heraclitus / Drew A. Hyland -- Justice, change, and knowledge: Aristotle, Parmenides, and Melissus on genesis and natural science / Rose Cherubin -- "As he says in his poetical way": Anaximander and Empedocles on the motive forces of kosmos / Phil Hopkins -- The human as (w)hole: Aristophanes's contest with Socrates in Clouds / Damian Stocking -- Classical Greek philosophy: Plato and Aristotle : Erós and eris: love and strife in ancient Greek thought and culture / John Russon -- Plato and Aristotle: more than a question of 'separate forms' / Francisco J. Gonzalez -- Measure, excess, and the all: To Agathon in Plato / Claudia Baracchi -- In the wake of Socrates: impossible memory / Walter Brogan -- The origins of political life in Plato's Republic and Laws / George Harvey -- Being in late Plato / Eric Sanday -- Aristotle on Physis: analyzing the inner ambiguities and transgression of nature / Marjolein Oele -- Human logos in Aristotle / Ömer Aygün -- Developing emotions: Aristotle's Rhetoric II.2-11 / Gregory Recco -- Hontina tropon gignetai philos: genesis versus alteration in the forming of friendships / John McCumber -- The political context for virtue: Aristotle's Politics / Eve Rabinoff -- Mimēsis: Plato and Aristotle on the political power of tragedy / Patricia Fagan -- The Hellenistic schools : Ataraxia: tranquility at the end / Pascal Massie -- A well-ordered world: the developing idea of kosmos in later Greek philosophy / Gina Zavota -- Searching for the 'why': Plotinus on being and the one beyond being / Michael Wiitala.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Philosophy, Ancient; Philosophie ancienne; PHILOSOPHY -- General; Philosophy, Ancient